Analysis of drug-induced and spontaneous cardioversions reveals similar patterns leading to termination of atrial fibrillation - van Hunnik, Arne; Sobota, Vladimír; Zeemering, Stef; Opacic, Dragan; Scaf, Billy; D’Alessandro, Elisa; Oyaert, Karel; Kuiper, Marion; Diness, Jonas G.; Sørensen, Ulrik S.; Milnes, James T.; van der Heyden, Marcel A. G.; et al. (Frontiers in Physiology, 2024)
Introduction The mechanisms leading to the conversion of atrial fibrillation (AF) to sinus rhythm are poorly understood. This study describes the dynamic behavior of electrophysiological parameters and conduction patterns leading to spontaneous and pharmacological AF termination. Methods Five independent groups of goats were investigated: (1) spontaneous termination of AF, and drug-induced terminations of AF by various potassium channel inhibitors: (2) AP14145, (3) PA-6, (4) XAF-1407, and (5) vernakalant. Bi-atrial contact mapping was performed during an open chest surgery and intervals with continuous and discrete atrial activity were determined. AF cycle length (AFCL), conduction velocity and path length were calculated for each interval, and the final conduction pattern preceding AF termination was evaluated. Results AF termination was preceded by a sudden episode of discrete activity both in the presence and absence of an antiarrhythmic drug. This episode was accompanied by substantial increases in AFCL and conduction velocity, resulting in prolongation of path length. In 77% ± 4% of all terminations the conduction pattern preceding AF termination involved medial to lateral conduction along Bachmann’s bundle into both atria, followed by anterior to posterior conduction. This finding suggests conduction block in the interatrial septum and/or pulmonary vein area as final step of AF termination. Conclusion AF termination is preceded by an increased organization of fibrillatory conduction. The termination itself is a sudden process with a critical role for the interplay between spatiotemporal organization and anatomical structure.